2019
DOI: 10.5306/wjco.v10.i9.300
|View full text |Cite
|
Sign up to set email alerts
|

Gangliocytic paraganglioma: An overview and future perspective

Abstract: Gangliocytic paraganglioma (GP) is rare neuroendocrine tumor (NET) with a good prognosis that commonly arising from duodenum. Although the tumor is characterized by its unique triphasic cells (epithelioid, spindle, and ganglion-like cells), the proportions of these three tumor cells vary widely from case to case, and occasionally, morphological and immunohistochemical similarities are found between GP and NET G1 (carcinoid tumors). Further, GP accounts for a substantial number of duodenal NETs. Therefore, GP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…However, diversity of GPs is different from relative consistence of NETs in morphology. More significantly, GPs have a more indolent clinical behavior and favorable prognosis than NETs ( 12 ). Thus, in our opinion, GP is supposed to be differentiated from NET G1.…”
Section: Discussionmentioning
confidence: 99%
“…However, diversity of GPs is different from relative consistence of NETs in morphology. More significantly, GPs have a more indolent clinical behavior and favorable prognosis than NETs ( 12 ). Thus, in our opinion, GP is supposed to be differentiated from NET G1.…”
Section: Discussionmentioning
confidence: 99%
“… 2 In one case, pancreaticoduodenectomy was performed for suspected malignancy because of an increase in tumor size prior to surgery; however, postoperative histopathological analysis revealed BGH, 5 which can be differentiated from leiomyoma, adenoma, lipoma, leiomyosarcoma, and carcinoid by performing EMR. 3 , 6 , 7 Some studies have suggested that BGH may have malignant potential; however, recurrence of BGH has not been reported. 8 Nevertheless, endoscopic resection may be an option in symptomatic patients or increasing tumor size.…”
Section: Discussionmentioning
confidence: 99%
“…GP is generally classi ed among NETs [7]. However, diversity of GP is different from relative consistence of NET in morphology, and GP has a more indolent clinical behavior and improved prognosis than NET [8]. Thus, GP is supposed to be differentiated from NET Grade 1.…”
Section: Discussionmentioning
confidence: 99%